Different effects of Atg2 and Atg18 mutations on Atg8a and Atg9 trafficking during starvation in Drosophila. Issue 3 (24th December 2013) - Nagy, Péter; Hegedűs, Krisztina; Pircs, Karolina; Varga, Ágnes; Juhász, Gábor
Abstract : The Atg2–Atg18 complex acts in parallel to Atg8 and regulates Atg9 recycling from phagophore assembly site (PAS) during autophagy in yeast. Here we show that in Drosophila, both Atg9 and Atg18 are required for Atg8a puncta formation, unlike Atg2. Selective autophagic degradation of ubiquitinated proteins is mediated by Ref(2)P/p62. The transmembrane protein Atg9 accumulates on refractory to Sigma P (Ref(2)P) aggregates in Atg7, Atg8a and Atg2 mutants. No accumulation of Atg9 is seen on Ref(2)P in cells lacking Atg18 or Vps34 lipid kinase function, while the Atg1 complex subunit FIP200 is recruited. The simultaneous interaction of Atg18 with both Atg9 and Ref(2)P raises the possibility that Atg18 may facilitate selective degradation of ubiquitinated protein aggregates by autophagy. Abstract : Atg9 and Atg18 are required for autophagy upstream of Atg8a, unlike Atg2. Atg9 accumulates on Ref(2)P aggregates in Atg8a, Atg7 and Atg2 mutants. Ultrastructurally, Atg9 vesicles cluster around Ref(2)P aggregates in stalled PAS. Atg9 does not accumulate on Ref(2)P upon loss of Atg18 or Vps34, while FIP200 does. Atg18 simultaneously interacts with both Atg9 and Ref(2)P.